"I sort of never felt like I should be worried about it or that I could be worried about it'" an interpretative phenomenological analysis of perceived barriers to disclosure by young people with coeliac disease. Issue 4 (16th May 2022) - Wheeler, Miranda; David, Annabel L.; Kennedy, Juliet; Knight, Matthew
Abstract: Objectives: There has been little research in the United Kingdom regarding young people's experiences of disclosure of psychological difficulties relating to coeliac disease (CD) to others, particularly healthcare professionals. This study sought to address this systematically with a focus on the lived experiences of young people with CD. This study aimed to gain insight into how paediatric gastroenterology services could improve the patient experience for those with CD and support the identification of patients who may benefit from further psychological support. Design: This study used interpretive phenomenological analysis (IPA) of patient accounts. Methods: Seven young people with CD (aged 11–16 years) were recruited from a UK hospital paediatric gastroenterology service. Semi‐structured interviews were carried out and verbatim transcripts were analysed using IPA to explore young people's experiences of CD and why they might feel able or unable to disclose psychological difficulties associated with their condition to clinicians. Results: Three superordinate themes were interpreted from the data. The first encapsulated experiences of adjusting to the diagnosis within a developmental context, including the role of adults in information provision and the importance of peer support. The second outlined experiences of managing perceived or actual stigma regarding others' perceptions of the condition and themselves. The third incorporated perceived barriers to disclosure relating to power, safety, and beliefs about the role of medical professionals. Conclusions: Findings highlight the importance of clinicians continually providing developmentally appropriate information to young people and actively breaking down barriers to disclosure through body language and the use of clear questions regarding emotional experiences.